Simultaneous Estimation Of Ivermectin, Albendazole & Diethylcarbamazine Citrate By Using Hplc (Journal of Namibian Studies : History Politics Culture, 2023)
Background: For the simultaneous assessment of the drugs Ivermectin (IVR), Albendazole (ALB), and Diethylcarbamazine Citrate (DEC) in combination, a new, straightforward, accurate, and stability-indicating HPLC (High-Performance Liquid Chromatography) approach was developed and validated.Results: The method was developed using a Zorbax SB Phenyl column (150 mm×4.6 mm, 3.5 μ) with gradient elution. 5 mM ammonium acetate with 0.1% Acetic Acid buffer and methanol with acetonitrile (50:50 v/v) was used as mobile phase with 1 mL per min flow rate at room temperature. The detection wavelength was fixed at 210 nm for DEC and 245 nm for ALB and IVR; the run time was within 15 min. The method was validated in terms of linearity, accuracy, robustness, and reproducibility. Calibration plots were linear over the 0.49-62.5 μg/ml range for IVR, 7.8-1000 μg/ml for ALB, and 15.625-2000 μg/ml for DEC. Recovery was in the 80-120% range with a relative standard deviation of less than 2% for both drugs. The limit of detection and the limit of quantification for the IVR were found to be 0.225 and 0.49 μg/ml respectively, for ALB it was 0.9 and 7.8 µg/ml and for DEC it is 7.8 and 15.63 μg/ml respectively.Conclusions: The combination of IVER, ALB, and DEC is used as mass drug administration for Lymphatic filariasis recommended by WHO. The developed HPLC method for the simultaneous estimation of Ivermectin, Albendazole, and Diethyl carbamazine is very robust and rugged thus this method can be used in the future for qualitative as well as quantitative analysis.